The Relationship of Redox With Hallmarks of Cancer: The Importance of Homeostasis and Context - Xing, Faliang; Hu, Qiangsheng; Qin, Yi; Xu, Jin; Zhang, Bo; Yu, Xianjun; Wang, Wei (Frontiers in Oncology, 2022)
Redox homeostasis is a lifelong pursuit of cancer cells. Depending on the context, reactive oxygen species (ROS) exert paradoxical effects on cancers; an appropriate concentration stimulates tumorigenesis and supports the progression of cancer cells, while an excessive concentration leads to cell death. The upregulated antioxidant system in cancer cells limits ROS to a tumor-promoting level. In cancers, redox regulation interacts with tumor initiation, proliferation, metastasis, programmed cell death, autophagy, metabolic reprogramming, the tumor microenvironment, therapies and therapeutic resistance to facilitate cancer development. This review discusses redox control and the major hallmarks of cancer.